Survey of Penetration Injuries Caused to Major Operation on Patients Refer to Tonekabon Shahid Rajaee Hospital, Mazandaran North of Iran during 2015-2016 - Pouya, M; Khodadadi, Babak; Khodadadi, V (Bangladesh Journal of Medical Science, 2018)
Introduction: Trauma is considered as one of the major causes of mortality in the World and in Iran. Which, many people die each year. The aim of study we evaluated penetrating traumas as Specific reason of deaths among affected patients. Materials and Methods: In this crosssectional retrospective study, 73patients with penetrating traumas visiting Shahid Rajaee hospital of Tonekabon in 2015-16were evaluated, then, the files were extracted from hospital archive files and information of patients such as age, sex, The type of agent and the cause of the injury, the reasons for the surgery and the type of surgery were recorded from the archived files, then, The data were statistically analyzed by the SPSS software. Results: Based on the findings, over the 60 (80 %) of patients were males, that was a significant relationship between sex and penetrating trauma. Also, the most common were penetrating trauma in the age group of 21-35 years old. There was a significant relationship between age and penetrating traumas (p<0.05), it should be noted that, other variables in this studies were not related significantly withthepenetrating trauma in patients. (p>0.05). Conclusion: The more common causes of penetrating traumas among young are Damage from driving accidents which require better Facilities to manage them. Also, the role of emergency rooms and the provision of equipment to reduce mortality from penetrating trauma can be mentioned. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.484-488